Analisis pendidikan karakter novel eiffel cooking battle dan relevansinya dengan materi pembelajaran PKN Sekolah Dasar - Annisa Fauzia; Septiyati Purwandari; Aditya Eska Wardana (Borobudur Educational Review, 2022)
This study aims to determine the values ​​of character education in the novel Eiffel Cooking Battle and the relevance of these characters to Civics learning materials for grade 4 elementary schools. This research is a type of qualitative descriptive research. Methods of data collection is done by using interviews and documentation. Sources of data taken from two data sources, namely primary data sources and secondary data sources. Primary data sources come from the novel Eiffel Cooking Battle by Zakiyah Artanti and Class 4 Thematic Textbooks Theme 1 Sub Themes 1 and 3. Secondary data sources come from interviews with expert lecturers in the field of character education and practitioners who already have a professional teacher competency certificate. The result of study indicate that there is a relevance between character education in the novel and the learning materials for grade 4 elementary school. Four character educations in the novel including religious, honest, disciplined and social care have relevance to the Civics class 4 learning material. Religious character education has relevance to the subject matter of ethnic, social and cultural diversity in Indonesia theme 1 sub theme 1 which instills religious character education such as being grateful for ethnic and cultural differences in Indonesia. Honest, disciplined and socially caring character education has relevance to the subject matter, examples of cooperation in diversity in theme 1, sub-theme 3, which instills the value of character education by providing examples of its application through illustrations or stories.